Learned changes in outcome associability - Quigley, Martyn (2020)
The ability to learn associations between events is of crucial importance for human and non-human animals. Without this ability we would be unable to identify when danger is imminent (e.g., the signs of a looming predator) or how to process the causal structure of our environment (e.g., understanding the role of causes and their corresponding effects). As such, it is essential to understand the factors which influence the formation of learned associations. Indeed, a plethora of studies have been conducted with this goal in mind and many models have been devised to elucidate the factors which influence how associative learning between events arises. A critical factor that a number of these models have identified concerns how the predictiveness of a cue, or a conditioned stimulus, can influence associative learning. For instance, studies have identified that a cue that has reliably predicted an outcome in the past, enters into subsequent associations better than a cue that has been an unreliable predictor of an outcome (e.g., the learned predictiveness effect; see Le Pelley & McLaren, 2003).